(untitled) (Research, Society and Development, 2020)
Malnutrition is a major challenge to be faced in the world, both in high-income, middle-income and low-income countries. Nutrition is influenced by the food systems that are responsible for the production, processing, distribution, preparation and consumption of food. However, food systems do not always provide a safe, high-quality diet for everyone. In addition, such diets are influenced by food environments, which concern the food sources available to consumers. Food environments can influence food choices, since they make food available to consumers. In this context, the work aimed to explain the relationship between the food environment and purchasing behavior. To answer this objective, an exploratory research with a qualitative approach was carried out, in which the methodological procedure used was bibliographic research. The results indicate that the food environment and consumption behavior are components that constitute food systems. These, in turn, correspond to the available food sources that influence people in making a purchase decision. Therefore, even if the individual presents preferences in the food choice process, the food environment will shape their consumption behavior.